The Impact of Professional Development About Weight-Related Issues for Pre-Service Teachers: A Pilot Study - Russell-Mayhew, Shelly; Ireland, Alana; Peat, Gavin (Alberta Journal of Educational Research, 2012)
Many teachers do not have a working knowledge of body image or weight issues. This pilot project examined body image satisfaction and eating/weight-related behaviours before and after a professional in-service with physical education pre-service teachers (N = 16). At the three- month follow-up, measures were repeated and qualitative data (critical incidents and a focus group) about the impact on teaching practice was collected. Results showed no significant changes, however pre-service teachers indicated (a) attempting to lose weight or gain muscle (despite many being in a healthy weight range), and (b) having a biased approach to weight-related issues. Pre-service teachers, particularly those specializing in physical education, are not immune to cultural messages that perpetuate the thin ideal. Future evaluation with a larger sample that formally measures implicit and explicit weight-bias is needed. Providing professional development for pre-service teachers may promote more positive practice about body image, weight-bias, and weight/eating-related concerns in schools. Plusieurs enseignants n’ont pas une connaissance pratique de l’image du corps ou des problèmes de poids. Ce projet pilote a porté sur la satisfaction quant à l’image corporelle et sur les comportements relatifs à l’alimentation et au poids avant et après une intervention professionnelle en cours de formation auprès de stagiaires en éducation physique (N = 16). Lors du suivi trois mois plus tard, on a répété des mesures et collecté des données qualitatives (incidents critiques et groupe de discussion) quant à l’impact sur la pratique pédagogique. Si les résultats n’indiquent aucun changement significatif, les stagiaires ont tout de même indiqué qu’ils (a) essayaient de maigrir ou d’augmenter leur masse musculaire, et (b) qu’ils avaient une approche biaisée par rapport aux questions liées au poids corporel. Les stagiaires, notamment ceux en éducation physique, ne sont pas insensibles aux messages culturels qui diffusent un idéal de minceur. Il faudra une autre évaluation avec un plus grand échantillon et des mesures formelles des préjugés implicites et explicites relatifs à la minceur. Offrir aux stagiaires des occasions de développement professionnel pourrait encourager une pratique plus positive quant à l’image du corps, aux préjugés relatifs au poids et aux préoccupations en matière de poids et d’alimentation dans les écoles.